PEMILIHAN MODEL PEMBELAJARAN YANG INOVATIF DALAM IMPLEMENTASI PEMBELAJARAN KURIKULUM MERDEKA DI DESA SUKABUNGAH - Putri Dewayanti, Natasya; Endah Sugiharti, Rini; Rikmasari, Rima (An-Nizam, 2024)
Innovative learning models are approaches taken in the learning process that involve creative ideas, technology and meaningful learning. Educators who have pedagogical competence are able to create innovative learning models for their students. This writing is made as a result of a seminar shown to elementary school teachers in Bojongmangu sub-district on the selection of innovative learning models. The selection of innovative learning models for teachers is shown so that in teaching and learning activities can achieve maximum learning objectives. In Bojongmangu sub-district, there are still many teachers who use textbook-centered learning models. After attending this seminar, elementary school teachers in Bojongmangu sub-district gained new insights into various innovative learning models that can be applied in the classroom and achieve maximum learning objectives.